Exclusão pela inclusão: a constituição de sentidos na educação especial - Souza, Catarina Rivadávia Silva de (2006)
This work, based on theoretical and analytical frameworks from Discourse Analysis (Pêcheux, 1969 and 1975, and Orlandi, 1983, 1990, 1999), expects to understand the senses produced about Special Needs people, especially the discourse on “general and unrestricted inclusion for all”. This study analyses the following materials: three posters of campaigns produced by Fundação Catarinense de Educação Especial (Special Education Foundation of Santa Catarina State, Brazil), three reports published by the diaries Diário de Santa Catarina, Diário do Nordeste and O Mossoroense, one report published in the magazine Gente Especial, and finally a paper presented at PUC/MG in the conference III Seminário Internacional Sociedade Inclusiva. With this research the intention is to contrast the senses built through these materials with those developed by the inclusion discourse